The primate EAE model points at EBV-infected B cells as a preferential therapy target in multiple sclerosis - Bert A 'T Hart; Sunil Anwar Jagessar; Krista eHaanstra; Ernst eVerschoor; Jon eLaman; Yolanda eKap (Frontiers in Immunology, 2013)
The remarkable clinical efficacy of anti-CD20 monoclonal antibodies (mAb) in relapsing-remitting multiple sclerosis (RRMS) points at the critical involvement of B cells in the disease. However, the exact pathogenic contribution of B cells is poorly understood. In this publication we review new data on the role of CD20+ B cells in a unique experimental autoimmune encephalomyelitis (EAE) model in common marmosets (Callithrix jacchus), a small-bodied neotropical primate. We will also discuss the relevance of these data for MS.Different from rodent EAE models, but similar to MS, disease progression in marmosets can develop independent of autoantibodies. Progressive disease is mediated by MHC class Ib (Caja-E) restricted cytotoxic T cells, which are activated by γ-herpesvirus-infected B cells and cause widespread demyelination of cortical grey matter. B-cell directed monoclonal antibody therapies (anti-CD20 versus anti-BLyS and anti-APRIL) have a variable effect on EAE progression, which we found associated with variable depletion of the EBV-like γ-herpesvirus CalHV3 from lymphoid organs. These findings support an important pathogenic role of CD20+ B cell in MS, especially of the subset infected with Epstein Barr virus (EBV).